An intracellular tube associated with feeding by Rotylenchulus reniformis on cowpea root - Razak, Abdul Rahman; Evans, A. A. F. (Brill Academic Publishers, 1976)

(untitled)
Rotylenchulus reniformis fed on modified pericyc1e tissue in cowpea roots. The feeding area extended six to fifteen cells on either side of the nematode head but a group of four to six cells closest to the nematode lips were obviously inter-connected by gaps in the radial walls, thus forming a functional unit (the feeding zone). The cell adjacent to the nematode lips (the feeding cell or initial syncytial cell) contained a feeding peg enclosing the nematode stylet. Opposite the stylet tip a hyaline tube (feeding tube) could be traced coiling helically in the feeding cell. Since the nematode head becomes immobile following establishment at a feeding site, the tube is thought to act as a filter through which the nematode may obtain cell solutes without cell particles that might block the stylet lumen.